THE ROLE OF INTERCULTURAL COMMUNICATION IN IMPROVING THE QUALITY OF HEALTH SERVICES: A LITERATURE REVIEW ON CULTURAL AWARENESS AND COMMUNICATION SKILLS AMONG MEDICAL PERSONNEL IN INDONESIA - Rizki Fauzi; Al-Amin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to examine the role of intercultural communication in improving the quality of health services in Indonesia through a literature review on cultural awareness and intercultural communication skills among medical personnel. In the context of Indonesia's multicultural society, health services require medical personnel to be able to interact with patients from various cultural backgrounds effectively, empathetically, and adaptively. This literature study collects and analyses various scientific sources, including journals, books, and research reports from the last 5 to 10 years. The results of the study show that cultural awareness is an important basis for medical personnel in understanding the values, beliefs, and health behaviours of patients, while intercultural communication skills play a role in translating this understanding into effective communication practices that respect differences. The integration of these two aspects has been proven to increase patient trust, satisfaction, and compliance with treatment, which ultimately strengthens the quality of healthcare services. This study recommends the need for policies and continuous training programmes that integrate intercultural communication competencies into the education system and professional practice of healthcare workers in Indonesia, thereby creating more inclusive, equitable, and humane healthcare services.